RELATIONSHIP BETWEEN STATISTICAL LITERACY AND MATHEMATICAL REPRESENTATION OF STUDENTS THROUGH COLLABORATIVE PROBLEM SOLVING MODEL - Johannis Takaria; Wahyudin Wahyudin; Jozua Sabandar; Jarnawi Afgani Dahlan (IKIP Siliwangi and I-MES, 2020)
The purpose of this study was to find out the relationship between statistical literacy and mathematical representation of students as pre-service elementary school teachers through the Collaborative Problem Solving (CPS) model. The relationship between statistical literacy and mathematical representation was analyzed by using a product-moment correlation with a sample of 35 students of Elementary School Teacher Education Study Program at one of the state universities in Ambon City. The results showed that there was a positive and strong relationship between statistical literacy and mathematical representation with a correlation value of 0.66. This relationship means that if students have good mathematical representation abilities, statistical literacy abilities are also getting better. Exploration of statistical literacy and mathematical representation abilities can be facilitated by using The CPS learning model. The CPS learning model can facilitate student learning as a structure in mathematical thinking so that statistical literacy and mathematical representation abilities of students can be explored through the transformation of ideas among students. The CPS learning model aspects were implemented in high and very high categories while the indicators were at rating-2 and rating-3.